The revenge of seven - Lore, Pittacus (Penguin Books, 2015)
The worst was supposed to be over. We were reunited after a decade apart. We were discovering the truth about our past. We were training and getting stronger every day. We were even happy. . . . We never imagined the Mogadorians could turn one of our own against us. We were fools for trusting Five. And now Eight is lost forever. I would do anything to bring him back, but that's impossible. Instead, I will do whatever it takes to destroy every last one of them. I've spent my entire life hiding from them, and they've stolen everything away from me. But that stops now. We're going to take the battle to them. We have a new ally who knows their weaknesses. And I finally have the power to fight back.